An Exercise for Use in Discussing Audit Evidence. - Shenkir, William G.; Tracy, John A. (The Accounting Review, 1971)
Abstract This article presents a proposed auditing exercise which can be used in discussing a taxonomy of evidence and evidence-gathering techniques. This exercise involves the use of a view-graph slide showing a scene that contains qualitative as well as quantitative characteristics. The particular slide that the author uses shows a profile of people riding on a bus or street car. The scene is fairly typical in that some people are standing while others are sitting, and the vehicle is carrying men, women and children of different races, some of whom appear to be engaged in conversation. This exercise is built on the maxim that a picture is worth a thousand words. The auditing instructor can develop any number of taxonomies to discuss evidence and its reliability. However, many students will probably not get the message. The exercise is a symbolic rather than logical means of communicating the message. It does not have to replace the professor's scholarly and logical explanation, but it can reinforce it. Three specific and relevant points can be made to auditing students in the discussion following their participation in the exercise. First, the evidence-gathering technique of observation can be evaluated. A second pedagogical point for which this exercise can be used is to discuss the variations in the reliability of audit evidence, especially testimonial evidence. A final pedagogical benefit of this exercise centers on the communication skill needed by the auditor.